Investigation of ferronickel slag powder for marine applications by using MIP method. (1st May 2022) - Shanmugasundar, G; Krishnan, Ganesh Sai; Babu, L Ganesh; Kumar, S; Makos, Mebratu
Abstract: The main aim of this work is to study the performance of the ferro-nickel slag in the powder form and to analyze the permeability performance using MIP method. The test is carried out under two different conditions. It is performed in clean water and a marine environment. Under these conditions different admixture conditions were examined. The change in impermeability of soil and cements for various admixture conditions were examined and the values were measured. A Mercury Intrusion Porosimeter (MIP) was used to examine the pore structure. Permeability values shown increasing trend in both clean water and in a marine environment. The Impermeability values shown increasing trend in marine environment compared with the clean water. During experimentation when Ferronickel slag powder exceeds 20 percentage. The impermeability reduces gradually and it gets decreased.40 percentages of ferronickel slag powder obtained were seemed to be optimum. Based on the results obtained from Mercury Intrusion Porosimeter (MIP), synergetic integration of ferro nickel slag powder on mixing with the soil-cement creates a micro-aggregate effect and the porosity of soil-cement which in turn increased the resistance for sea water erosions.